Cover crops and preemergence herbicides: An integrated approach for weed management in corn-soybean systems in the US Midwest - Grint, Kolby R.; Arneson, Nicholas J.; Arriaga, Francisco; DeWerff, Ryan; Oliveira, Maxwel; Smith, Daniel H.; Stoltenberg, David E.; Werle, Rodrigo (Frontiers in Agronomy, 2022)
Adoption of a fall established, high biomass cereal rye cover crop has potential to diversify weed management in corn and soybean production systems, reducing the selection pressure for resistance to postemergence herbicides. However, farmers and crop consultants express concern about limited weed suppression from an overwintering cover crop in areas where high biomass production is limited by cooler spring temperatures, such as in the upper Midwest U.S. Use of a preemergence herbicide, regardless of cover crop adoption, is a standard recommendation for improving early season weed control in corn and soybean. Field experiments were conducted at two sites in Wisconsin to assess the effects of six soil management practices (tillage, no-till, and four cereal rye cover crop termination timings/methods) paired with the use of a preemergence herbicide on weed suppression at the time of postemergence herbicide application and crop productivity. Results showed that cereal rye biomass increased > 6x between termination at the time of cash crop planting versus termination two weeks later. In corn and soybean, weed ground cover was lower for soil management with cereal rye cover crop terminated two weeks after cash crop planting (≤ 7% weed cover) compared to all other soil management practices (≥ 23% weed cover) when a preemergence herbicide was not used. Use of a preemergence herbicide resulted in low weed ground cover across treatments in corn (≤ 7% weed cover) and soybean (≤ 13% weed cover). Corn and soybean yield was not affected by preemergence herbicide treatments. Corn yield was lower at the south-central Wisconsin location for the soil management with a cereal rye cover crop terminated two weeks after cash crop planting (9.82 Mg ha-1) compared to all other soil management practices (≥ 12.07 Mg ha-1); at the southwest Wisconsin location, corn yield was greater for the conventional tillage treatment (14.28 Mg ha-1) compared to all other soil management treatments (≤ 10.89 Mg ha-1). Soil management did not affect soybean yield, although yields were different between locations with 3.44 Mg ha-1 at the south-central Wisconsin compared to 4.77 Mg ha-1 at the southwest Wisconsin location.